The accuracy of preoperative imaging in measuring the length of the ileocolic segment affected by Crohn's disease: a prospective cohort study. (May 2017) - Brouquet, A.; Rangheard, A.‐S.; Ifergan, J.; Lazure, T.; Carbonnel, F.; Penna, C.; Benoist, S.
Abstract: Aim: The study aimed to evaluate the accuracy of imaging for measurement of the length of the ileocolic segment affected by Crohn's disease. Method: Fifty‐four consecutive patients who underwent resection between 2011 and 2014 for ileocolic Crohn's disease were prospectively studied. All had preoperative MR or CT enterography. Two independent radiologists measured the length of the diseased intestinal segment. The measurements were compared with the length of disease assessed on pathology of the non‐fixed surgical specimen. Results: The median preoperative length of the Crohn's disease segment on imaging was 20.5 (2–73) cm and 20 (3–90) cm, as measured by the two radiologists. Interobserver agreement was substantial (κ = 0.69) with a correlation coefficient ( r ) of 0.82 ( P < 0.001). The median length of the Crohn's disease segment on pathological examination was 16.5 (2–75) cm and was closely correlated with the radiological measurement ( r = 0.76, P < 0.001). The length of the Crohn's disease segment on imaging was correct to within 5 cm of the value on pathology. It was correct in 30 (55%) patients and was underestimated and overestimated in 6 (11.1%) and 18 (33.3%). A length of disease of less than 20 cm found on imaging in 26 patients was confirmed in 25 (96%) on pathology, whereas a length of more than 20 cm found on imaging in 28 patients was confirmed in 18 (64%) on pathology. The sensitivity, specificity, positive predictive value, negative predictive value and overall accuracy of imaging for predicting a length of less than 20 cm were 71%, 95%, 96%, 64% and 79%. Conclusion: Imaging accurately identifies the length of the ileocolic segment of Crohn's disease when it is 20 cm or less on pathological examination. In patients with more extensive disease, imaging tends to overestimate the length and should be interpreted with caution.